Development and characterization of seed gums from Tamarindus indica and Cassia fistula as disintegrating agent for fast disintegrating Thai cordial tablet - Kampanart Huanbutta; Wancheng Sittikijyothin (Elsevier, 2017)
Crude seed gum and their carboxymethyl derivatives from Tamarindus indica and Cassia fistula seeds were developed and characterized to apply as the pharmaceutical disintegrant in fast disintegrating Thai cordial tablet. The chemical structure of crude gum was chemically modified via carboxymethylation. Degree of substitution (DS) of carboxymethylated gums was determined. Carboxymethylated gums with minimum and maximum DS values were chosen for further application. IR absorption spectra of gum samples were observed to verify their chemical structure changes. In physical properties, the intrinsic viscosity and swelling property of all gum samples were evaluated. The results showed that carboxymethylated gums had higher intrinsic viscosity than those of crude gum. Moreover, they could swell and be soluble in cold water better than those of crude gums. In conclusion, the modified gums from both plants could provide higher hardness and be better used than that crude gums for fast disintegrating Thai cordial tablet. However, this is a preliminary assessment to expressing pharmaceutical application possibility of these gums as disintegrants, diluents and drug release controlling agents.